A Conceptual Framework for Exploring the Impacts of Corporate Social Responsibility on Employee Attitudes and Behaviour. (October 2015) - Santhosh, Manimegalai; Baral, Rupashree
This article develops a conceptual framework that explains how organizations can influence employees' attitudes and behaviour through their corporate social responsibility (CSR) activities. There are plenty of studies to suggest the financial benefits of CSR. However, studies are scarce to link CSR with non-financial measures of organizational effectiveness, such as, affective commitment, job engagement and organizational citizenship behaviour (OCB). Moreover, studies are rare to delineate the process through which CSR can bring positive attitudes. Thus, this article focuses on organizational prosocial identity as a mediating variable. The role of communicating CSR activities is almost negligible and to address this gap, this article considers CSR communication as a moderating variable. Drawing from literature, this article argues that the success of an organization lies in enhancing positive attitudes among employees and probably, one of the ways to promote this is through CSR. Based on this assertion, the framework identifies CSR activities towards four stakeholders (employees, customers, community and environment) and its impacts on employees. Several research implications are proposed based on the propositions highlighted in this article.